Physicochemical properties of sorghum malt and Bambara groundnut based extrudates - Filli, Kalep Bulus (Journal of Food Science and Technology Nepal, 2016)
Extrusion cooking has beenused as an important technique for the manufacture and modification of widevariety of food products such as expanded snack foods, ready-to-eat cerealswhich are made from foods with high starch and protein. Although starchy foodsare the predominant structure forming agents, their utilization as food hasbeen limited by their poor protein quality and quantity. The supplementationwith legumes improves the essential amino acid content of the food. Bambaragroundnut has balanced amino acid content and can supplement the quality ofamino acids in sorghum. Starch from sorghum flour has been found to beresistant to extrusion. This makes the modification of functional propertiesvery difficult. Malting of the sorghum has been adopted for the modification ofthe starch quality. The nutrient and functional properties of food play majorrole in their application and use as food. This work has studied the effect offeed moisture (20%, 25%, and 30%) and barrel temperature (100o C,110OC and 130o C) on the chemical composition andfunctional properties of sorghum malt and Bambara groundnut blends. From theresults of the analyses, protein content varied from 11.07% to 11.75%. Increasein barrel temperature decreased the protein content while feed moistureincrease favoured the retention of proteins. The expansion index (EI), waterabsorption index (WAI) and effect of quantity of water on swell volume (EQWSV)varied from 1.88 to 3.88, 570% to 660% and 13.7 seconds to 33.4 secondsrespectively. These properties are negatively affected by increase in feedmoisture but they improve with increases in barrel temperature. The values forwater solubility index (WSI), bulk density and Wettability ranged from 2.2% to8.4%, 0.2g/cm3 to o.7g/cm3 and 14.3 seconds to 37.3seconds respectively. The increase in feed moisture has positive influence onthese parameters while temperature increased affected them negatively.